2017
DOI: 10.1021/acs.jafc.6b05764
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Fertilizer-Induced Increase of Symbiotic Microorganisms Improves Forage Growth and Quality

Abstract: Magnesium (Mg) plays important roles in photosynthesis and protein synthesis; however, latent Mg deficiencies are common phenomena that can influence food quality. Nevertheless, the effects of Mg fertilizer additions on plant carbon (C):nitrogen (N):phosphorus (P) stoichiometry, an important index of food quality, are unclear and the underlying mechanisms unexplored. We conducted a greenhouse experiment using low-Mg in situ soil without and with a gradient of Mg additions to investigate the effect of Mg fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
5
23
3
Order By: Relevance
“…Magnesium (Mg) is the key element of chlorophyll (Chen et al 2017) and iron (Fe) is used for chlorophyll formation (Miller et al 1984). Silicon may induce internal Fe and Mg transport, leading to the synthesis of chlorophyll.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium (Mg) is the key element of chlorophyll (Chen et al 2017) and iron (Fe) is used for chlorophyll formation (Miller et al 1984). Silicon may induce internal Fe and Mg transport, leading to the synthesis of chlorophyll.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of nutrients present in growth media on Rhizobium -legume symbioses and nitrogen fixation have been reported (Olivera et al, 2004 ; Chaudhary et al, 2008 ). Rhizobia require adequate mineral nutrients, such as carbon, nitrogen, phosphorus, potassium, magnesium, and several microelements for the metabolism involved in invading and successfully colonizing the host root system in order to establish an effective legume-plant host symbiosis (Paliya et al, 2014 ; Egamberdieva et al, 2016 , 2017 ; Chen et al, 2017 ). In the rhizosphere, high competition for nutrients and niches occurs among various kinds of organisms, including the indigenous microflora, and rhizobia colonization depends on nutrient availability (Kuzyakov and Xu, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg), phosphorus (P), and nitrogen (N) are essential nutrient elements in plant growth and development and are involved in photosynthesis, nucleic acid metabolism, protein synthesis, enzyme activity, carbohydrate metabolism, and nitrogen fixation (Qin et al, 2012 ; Niste et al, 2014 ; Chen et al, 2017 ). The conversion of atmospheric N into ammonium (NH 4 ), which is available to plants through the intervention of rhizobia, requires P as an essential component (Dakora and Keya, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Choudhury and Khanif also showed that the effects of soil, N and Mg on total Mg uptake (grain and straw) were significant in rice. Chen et al . explained that an adequate supply of Mg could significantly increase Mg concentrations of leaves in maize.…”
Section: Discussionmentioning
confidence: 99%
“…52 Choudhury and Khanif 53 also showed that the effects of soil, N and Mg on total Mg uptake (grain and straw) were significant in rice. Chen et al 54 explained that an adequate supply of Mg could significantly increase Mg concentrations of leaves in maize. However, Gaj et al 14 demonstrated that mineral fertilization with appropriate levels of K and P significantly influenced Mg accumulations in maize organs, except for the cob cores.…”
Section: Effects Of Mg Application On the Distributions Of Mg In The mentioning
confidence: 99%